2023
DOI: 10.1038/s41529-023-00386-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface modification on interfacial behavior in bioabsorbable magnesium wire reinforced poly-lactic acid polymer composites

Abstract: The mechanical behavior, corrosion mechanisms, and cytocompatibility at the interface of magnesium wires reinforced poly-lactic acid polymer composites were studied by in vitro degradation study of 180 days. Surface modification of Mg wires by plasma-electrolytic oxidation improved the interface shear strength from 10.9 MPa to 26.3 MPa which decreased to 8 MPa and 13.6 MPa in Mg/PLA and PEO-Mg/PLA composites, respectively, after 42 days of in vitro degradation. Cross-sections of the composite showed good cytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Interestingly, the theoretical volume of hydrogen expected to be released from the Mg content in the composite was 84.6 mL, much higher than the 47 mL measured experimentally. This difference is in agreement with previous reports 45,46 and has been attributed to oxygen reduction reactions likely to occur during slow corrosion of Mg 47,48 or that the hydrogen bubbles were trapped underneath the sample or in the funnel. 45 Scanning electron microscopy was used in order to reveal the degradation mechanisms involved of the three materials over time.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, the theoretical volume of hydrogen expected to be released from the Mg content in the composite was 84.6 mL, much higher than the 47 mL measured experimentally. This difference is in agreement with previous reports 45,46 and has been attributed to oxygen reduction reactions likely to occur during slow corrosion of Mg 47,48 or that the hydrogen bubbles were trapped underneath the sample or in the funnel. 45 Scanning electron microscopy was used in order to reveal the degradation mechanisms involved of the three materials over time.…”
Section: Discussionsupporting
confidence: 93%
“…It has also been shown that the polymer matrix is subjected to an accelerated degradation in alkaline environment, even more than in an acidic environment. 48,50,55 Furthermore, increasing the volume of the particle due to Mg oxidation leads to crack formation and facilitates the entry of water in the case of PLDL + Mg + PEG. 49 A similar process was observed, although at a slower rate, in the PLDL + Zn composite.…”
Section: Discussionmentioning
confidence: 99%